Medición del diámetro de la vaina del nervio óptico por ultrasonido transorbital en pacientes con preeclampsia. - Ruiz Castro, Juan Carlos; Martinz, Adriana; Reyes, Osvaldo (Ginecología y Obstetricia de México, 2025)
OBJECTIVE: To determine the differences in optic nerve sheath diameter between patients with severe pre-eclampsia and pregnant women with normal blood pressure, and to establish a cut-off value that can be used to determine the diagnosis and risk associated with this alteration. MATERIALS AND METHODS: Prospective case-control study conducted from October to December 2022 in the Obstetrics Department of the Maternity Unit of the Santo Tomás Hospital, Panama. Inclusion criteria: pregnant patients between 18 and 40 years of age and between 34 and 40 weeks of gestation. The case group included patients hospitalized for pre-eclampsia with severity criteria. Qualitative variables were reported as frequencies and percentages, quantitative variables as means and standard deviations. Mann-Whitney U and χ² tests were used for statistical analysis. RESULTS: We compared 53 patients with pre-eclampsia with severity criteria and 53 with normal blood pressure. In the former, the optic nerve sheath diameter was found to be significantly larger compared to patients with normal blood pressure (pre-eclampsia: 5.42 ± 0.68 mm vs. normal blood pressure: 4.42 ± 0.34 mm; p < 0.00001). ROC curve analysis showed that the best cut-off value for optic nerve head diameter to diagnose severe pre-eclampsia was 5.05 mm (sensitivity: 75.5%, specificity: 100%). No statistically significant difference was observed in pregnant women with pre-eclampsia according to the presence or absence of neurological symptoms (headache) with respect to optic nerve sheath diameter (p = 0.32). CONCLUSION: Pregnant women with pre-eclampsia with severe criteria have a larger optic nerve sheath diameter compared to patients without blood pressure abnormalities.